2018
DOI: 10.5812/ijem.66979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restraint Stress on Plasma PTH Concentration and Its Molecular Targets Expressions in Wistar Rats

Abstract: BackgroundThere are limited numbers of experimental studies related to the potential role of parathormone/parathyroid hormone (PTH) in response to psychological stress. In the current study, we aimed to cross-examine, for the first time, changes in PTH plasma concentration and the expression of its molecular targets mediated by restraint stress in rats.MethodsMale Wistar rats (n = 42) were separated into control and stressed groups. They were further divided into two groups that received chronic restraint stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Parathyroid hormone (PTH) is an essential regulator and minute-to-minute determinant of both extracellular and intracellular calcium homeostasis in the blood 89 . Using a murine model of restraint stress, Terzioqlu et al demonstrated that psychological stress increases plasma PTH level by upregulating the calcium-sensing receptor on the chief cells in the parathyroid glands 90 . The actions of PTH in the body are bi-directional 91 .…”
Section: Factors Mediating the Relationship Between Psychological Strmentioning
confidence: 99%
“…Parathyroid hormone (PTH) is an essential regulator and minute-to-minute determinant of both extracellular and intracellular calcium homeostasis in the blood 89 . Using a murine model of restraint stress, Terzioqlu et al demonstrated that psychological stress increases plasma PTH level by upregulating the calcium-sensing receptor on the chief cells in the parathyroid glands 90 . The actions of PTH in the body are bi-directional 91 .…”
Section: Factors Mediating the Relationship Between Psychological Strmentioning
confidence: 99%
“…Small sample sizes and heterogeneous patient populations may explain these inconsistent findings. Likewise, findings may be confounded by elevations of PTH due to critical illness ( 55 , 56 ).…”
Section: Mechanisms Of Mineral Dysregulation In Akimentioning
confidence: 99%
“…The molecular, cellular, and biochemical mechanisms behind the relationship between PTH and mental health are not known. Recently, however, PTH levels were shown to negatively correlate with plasma corticosterone levels after acute restraint stress (176). In addition, a significant reduction in parathyroid hormone receptor 1 (PTHR1) levels in both the kidney and thyroid was observed in rats exposed to chronic (28-day) daily restraint stress.…”
Section: Interaction Of Treatmentsmentioning
confidence: 99%